Arctic Disequilibrium: Shifting Human-Environmental Systems. (July 2019) - Veldhuis, Djuke; Tejsner, Pelle; Riede, Felix; Høye, Toke T.; Willerslev, Rane
This special issue of Cross-Cultural Research presents four papers each of which in their own way addresses the question of how Arctic populations tackle the high levels of unpredictability and risk associated with their environment. It takes as a starting point the evidence for and against aspects of disequilibrium between humans, animals, and their environment. The authors consider both contemporary and historical Indigenous Arctic populations and the dynamics of human–animal relations in the context of an ever-changing socioecology of the Arctic. Three overarching sources of disequilibrium are identified: (a) disruption in existing ecological networks due to climate and environmental upheaval, (b) effects of sociopolitical change (including migration and disease), and, finally, (c) changes to subsistence strategies. Based on contemporary field studies from across the Arctic, including the Ust'-Avam and Samoyed from the Taimyr Region in Russia, Sami in Finland, Yukagir and Chukchi from Siberia, and the historic Thule community from Greenland, the authors illustrate how, despite apparent disequilibria, there is nevertheless notable resilience evident in the coupling of human-environmental systems. Documenting past and present changes in local livelihoods, subsistence patterns, and sociocultural practices helps us understand the wider context in which these cultures persist. It also allows us to explore what factors are significant in supporting the long-term resilience of Indigenous communities, especially in the context of challenges, such as high levels of addiction, depression and suicide, facing contemporary arctic societies.